HBR's 10 must reads on managing people - Goleman, Daniel (HBR's 10 must reads (Series), 2022)
Managing people is fraught with challenges-even if you're a seasoned manager. Here's how to handle them. If you read (or listen to) nothing else on managing people, listen to these ten articles (featuring "Leadership That Gets Results," by Daniel Goleman). We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you maximize your employees' performance. HBR's 10 Must Reads on Managing People will inspire you to: tailor your management styles to fit your people; motivate with more responsibility, not more money; support first-time managers; build trust by soliciting input; teach smart people how to learn from failure; build high-performing teams; and manage your boss. This collection of bestselling articles includes: featured article "Leadership That Gets Results" by Daniel Goleman, "One More Time: How Do You Motivate Employees?," "The Set-Up-to-Fail Syndrome," "Saving Your Rookie Managers from Themselves," "What Great Managers Do," "Fair Process: Managing in the Knowledge Economy," "Teaching Smart People How to Learn," "How (Un)ethical Are You?," "The Discipline of Teams," and "Managing Your Boss."